Penyuluhan Pembuatan Permen dan Teh dari Kayu Manis di Kelurahan Antirogo Kabupaten Jember - Dina Trianggaluh Fauziah; Dyan Wigati; Ayu Angger Putri M. Sholeh; Moch Rafa Firdaus; Brian Sapta Nuriandra; Ika Oktavianawati; Atok Ainur Ridho (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
The use of natural ingredients as medicine has been practiced since ancient times as a means of maintaining health, preventing disease, and treating illness. Natural materials such as cinnamon contain secondary metabolites such as flavonoids and polyphenols, which are believed to have anti-inflammatory, antibacterial, antioxidant, and anticancer properties. The purpose of this community service activity is to teach the community how to make cinnamon-based candy and tea that can be consumed by children and adolescents. The method used is material counseling followed by activity evaluation. The results of the evaluation of this community service activity showed that 92% of participants were satisfied with the material provided by the implementation team. This also shows that the educational material provided can give new information and benefits to the community. It is hoped that this activity can be applied by the community and that community service activities can be carried out regularly in the area to increase the local community's knowledge about the use of natural ingredients.